2021
DOI: 10.1017/brimp.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the impact of BRAINSPaN: a multidisciplinary community of practice for clinicians and researchers in the brain impairment field

Abstract: Background: Communities of practice can facilitate the sharing and translation of knowledge. BRAINSPaN is a multidisciplinary community of practice of clinicians, researchers and students in the brain impairment field that was launched in Australia in June 2017. We aimed to investigate the impact of BRAINSPaN on multidisciplinary collaboration and on knowledge, skills and confidence in domains of practice of interest to members. Methods: We surveyed BRAINSPaN members over three time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…One way is to join communities of practice like BRAINSPaN (). Our survey of BRAINSPaN participants (Wong, Steel, et al, 2022b) found that increasing interaction with others in the brain impairment field was one of their main goals for participation, and they reported having achieved that goal when we surveyed them again a few months later. These online communities of practice are easy to join and enable us to communicate quickly and efficiently to share knowledge.…”
Section: Thinking Small and Big: How To Join Up Collaborate And Integ...mentioning
confidence: 99%
“…One way is to join communities of practice like BRAINSPaN (). Our survey of BRAINSPaN participants (Wong, Steel, et al, 2022b) found that increasing interaction with others in the brain impairment field was one of their main goals for participation, and they reported having achieved that goal when we surveyed them again a few months later. These online communities of practice are easy to join and enable us to communicate quickly and efficiently to share knowledge.…”
Section: Thinking Small and Big: How To Join Up Collaborate And Integ...mentioning
confidence: 99%